DUKUNGAN PENGEMBANGAN KARIR DAN PEMBERDAYAAN OLEH KEPALA SEKOLAH SERTA KONTRIBUSNYA TERHADAP KEPUASAN KERJA GURU - Jumroh; Dekawati, Ipong (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2020)
In general, teachers work to get satisfaction in carrying out their work. Satisfaction at work encourages the emergence of enthusiasm in work so that it tends to perform well. Many factors affect job satisfaction, including career development support and empowerment by the principal. The focus of the research is on how much the contribution of career development support and empowerment by the principal to teacher job satisfaction. The research method used is descriptive and verification methods, with data collection techniques using a Likert scale questionnaire, to the teacher. Processing of research results using regression analysis techniques. The significance test uses the F-test. The results showed that: (1) There was a positive and significant contribution of career development support to teacher job satisfaction. (2) There is a positive and significant contribution of empowerment by the principal to job satisfaction. (3) There is a positive and significant contribution to the support of career development and empowerment by the principal simultaneously to teacher job satisfaction. Considering that job satisfaction is very important in order to increase work motivation and school productivity, teachers as the most members of the education unit should be given even greater opportunities to grow followed by adequate funding assistance so that their careers develop more in the hope that teachers feel more satisfied at work. It is recommended to give more responsibility to the teacher so that the teacher unconsciously enters the empowerment process. Teachers should be alternately assigned to manage various activities with the authority to make decisions with the permission of the school principal. It is hoped that the teacher will develop his insight and confidence, which in turn can increase the level of satisfaction at work.